HUBUNGAN C-REACTIVE PROTEIN DENGAN PEMANJANGAN PROTHROMBIN TIME PADA PASIEN SIROSIS HATI YANG MENGALAMI PERDARAHAN SALURAN MAKANAN BAGIAN ATAS - Mariadi, IK; Wibawa, IDN; Purwadi, N; Suryadarma, IGA (journal of internal medicine, 2011)
Bacterial infections are common complications in cirrhosis, and cause the systemic in! ammation process. The natureof the relationship between gastrointestinal bleeding and infection in cirrhosis has not been clari